Introducing Market-oriented Horticulture Farming in Refugee Hosting Areas of Uganda: An Intervention that Builds Resilience against Future Emergency - Takeshima, Hiroyuki (2021)
Hiroyuki Takeshima SPECIAL EVENT UNFSS Independent Dialogue: The Critical Role of Agricultural Extension in Advancing the 2030 Agenda: Lessons from the Field and Empirical Evidence Co-Organized by IFPRI and Sasakawa Africa Association (SAA)